2005
DOI: 10.1016/j.jenvman.2004.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The development of a UK kerbside scheme using known practice

Abstract: Local authorities in the UK have been set challenging new targets for recycling household waste for 2005. This means many of them are urgently trying to determine which parameters in kerbside schemes are most important for increasing recycling rates. In this work information from previous kerbside schemes is used to plan significant improvements in an existing scheme in Horsham District, UK, and trialled using 1,000 homes including a control group. It used fortnightly collection of residual waste with sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 14 publications
(15 reference statements)
3
29
0
Order By: Relevance
“…Martin et al, [53] reported that if individual perceived a lack of recycling facilities and local collection, he/she may likely not participate in recycling. Other studies have also revealed absolutely consistent results on the role of recycling facilities and local collection in influencing residents' intention toward recycling [41,43,54,55].…”
Section: The Role Of Facilitating Conditionsmentioning
confidence: 61%
See 1 more Smart Citation
“…Martin et al, [53] reported that if individual perceived a lack of recycling facilities and local collection, he/she may likely not participate in recycling. Other studies have also revealed absolutely consistent results on the role of recycling facilities and local collection in influencing residents' intention toward recycling [41,43,54,55].…”
Section: The Role Of Facilitating Conditionsmentioning
confidence: 61%
“…Also, a study by Miafodzyeva and Brandt [43] revealed that access to curbside collection positively influences residents' waste recycling intention. Other studies also reported that access to curbside station influence recycling behavior and increase recycling of all type of materials [41,54,55]. Thus, households with better access to local collection tend to recycle more, also, a good location of recycling collection stations not far from the households may influence recycling behavior [76].…”
Section: Testing the Moderating Effects Of Perceived Lack Of Facilitamentioning
confidence: 91%
“…All sources analysed (Fig. 6) report that access to kerbside recycling stimulates recycling behaviour and increases recycling of all material types [4,9,22,26,49,54,61,62]. According to the authors, this indicates that recycling based on any system other than kerbside (property closed) collection (mostly drop-off stations involving storage, time and transport costs for individuals) can lower participation.…”
Section: Technical-organisational Group Of Variablesmentioning
confidence: 97%
“…14 Previous studies have pointed to cause and effect relations between improved recycling schemes and improved recycling rates (Williams and Cole, 2013;Woodard et al 2005). …”
Section: Insert Figure 3 Herementioning
confidence: 99%